The Price of Belonging: Price Setting in the Market for Champagne Grapes - Ody-Brasier, Amandine (Organization Science, 2023)
Various studies show that social relations between exchange partners affect price setting behaviors. Although scholars expect a broad range of buyer–seller relations to shape price—and different types of relations to have different effects—we have surprisingly little quantitative evidence for these views. This is in part because extant empirical work operationalizes relations rather narrowly, focusing on repeated exchange relations. Drawing on existing theory and fieldwork in the market for Champagne grapes, this paper investigates how community relations and repeated exchange shape price setting behavior. I use unique transaction-level price data to document the effects of these two types of buyer–seller relations. I find that community relations reduce deviations from local pricing norms such that, for an average transaction, grape sellers charge about €1,500 less when the buyer belongs to their village or school district. I draw on rich qualitative data to illustrate what is driving these effects. Interviews reveal not only that social relations infuse in the exchange a logic of action at odds with the logic of markets, but also, importantly, that there is some heterogeneity within the embedded logic of exchange. In particular, community relations appear to be more constraining than repeated exchange for price setters. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.1564 .